Reconfigurable field programmable gate arrays for mission-critical applications - Battezzati, Niccolò (Springer New York, 2011)
Embedded systems applications that are either mission or safety-critical usually entail low- to mid- production volumes, require the rapid development of specific tasks, which are typically computing intensive, and are cost bounded. The adoption of re-configurable FPGAs in such application domains is constrained to the availability of suitable techniques to guarantee the dependability requirements entailed by critical applications. This book describes the challenges faced by designers when implementing a mission- or safety-critical application using re-configurable FPGAs and it details various